Analysis of QT Dispersion, Corrected QT Dispersion, and P-Wave Dispersion Values in Alcohol Use Disorder Patients With Excessive Alcohol Use - Baykara, Sema; Ocak, Davut; Berk, Şule Şirin; Köroğlu, Sedat (Physicians Postgraduate Press Inc., 2020)
Objective: To identify the changes in QT dispersion (QTd), corrected QTd (QTcd), and P-wave dispersion (Pd) values with long-term alcohol abuse that could lead to severe ventricular arrhythmia, atrial fibrillation, and sudden death in alcohol use disorder (AUD) patients with excessive alcohol use. Methods: This cross-sectional study included 48 individuals diagnosed with AUD based on DSM-5 criteria. Patients with a history of psychiatric diseases were not included. The control group comprised 48 individuals with no psychiatric diagnosis who did not abuse alcohol or other substances. Participants with body mass index > 24.9 kg/m2 were excluded. Twelve-derivation electrocardiograms (ECG) were obtained from all participants. Results: The mean ± SD age was 44.35 ± 10.24 years in the AUD group and 40.90 ± 13.45 years in the control group. There was no significant difference between the groups based on age (P = .108). There was a significant difference between the groups based on smoking status (P = .000). The mean ± SD period of alcohol use was 20.71 ± 12.04 years, and the alcohol intake was 5.88 ± 1.65 units/d. The AUD group demonstrated elevations in all ECG measures (QTd: 46.56 vs 26.67 ms, QTcd: 54.25 vs 30.88 ms, Pd: 44.69 vs 28.54 ms, all P = .000). Conclusions: AUD patients with excessive alcohol use had a higher risk of arrhythmia and sudden death compared to the control group. Consideration of ECG and referral to cardiologic examinations would contribute to the follow-up and health of patients with AUD. © 2020 Physicians Postgraduate Press, Inc.
Keywords: Adult; Alcohol-Induced Disorders; Alcoholism; Arrhythmias, Cardiac; Cross-Sectional Studies; Death, Sudden, Cardiac; Electrocardiography; Humans; Male; Middle Aged; Risk; adult; alcoholism; complication; cross-sectional study; electrocardiography; heart arrhythmia; human; male; middle aged; pathophysiology; risk; sudden cardiac death